The Role of Credit Risk, Liquidity, and Capital in Influencing Banking Profitability in Indonesia, 2020–2024 - Ella Fitriana; Dian Prawitasari; Usman Usman; Fakhmi Zakaria (Journal of Management Economics and Financial Accounting, 2026)
This investigation is intended to evaluate the impact of Credit Quality Ratio (NPL), Funding Utilization Ratio (LDR), and Capital Buffer Indicator (CAR) regarding the earnings capability of banks traded on the Indonesia Stock Exchange within 2020–2024. The investigation utilized an explanatory quantitative design supported by panel data regression techniques. The observed sample included 23 banks determined by purposive sampling, generating 110 research observations. Estimation was performed using the Stochastic Effects Approach (SEA) combined with Estimated Generalized Least Squares (EGLS) and robust standard errors for overcoming heteroscedasticity and autocorrelation problems. Findings reveal that NPL exerts a significant detrimental impact on earnings performance measured through ROA. LDR shows no significant relationship with ROA, suggesting that loan expansion alone cannot directly enhance profitability when credit quality remains insufficient. Conversely, CAR demonstrates a meaningful improvement in ROA, suggesting stronger capital resilience strengthens banks in creating earnings. Collectively, NPL, LDR, and CAR exert a significant influence on profitability, reflected by an Adjusted R-squared of 40.68%. The results suggest that preserving credit quality and reinforcing capital adequacy constitute crucial measures to enhance banking profitability in Indonesia.